Commentary: The Relationship of Antitrust Policy and Technological Progress - James T. Halverson (Washington University Law Quarterly, 1975)
It is the purpose of this Commentary to explore, in a preliminary fashion, the relationship of antitrust policy and technological innovation and to suggest circumstances under which the antitrust laws may lend themselves to the enhancement of opportunities for technological change and progress.
Keywords: Antitrust law; Technology